Service Quality Perception of Customers – a Study of Toyota Motors in India - Baber, Hasnan (Organizations and Markets in Emerging Economies, 2018)
The study is aimed to explore the gap between the level of expectation in service quality and service perception and its influence on customer satisfaction of Toyota customers in India. A 25-item questionnaire was used to collect primary data from 1721 customers of selected states. Data was statistically analysed through reliability analysis, exploratory factor analysis, paired sample t-test and confirmed factor analysis. Structural equation modelling was employed to measure the relation of actual service received and customer satisfaction. The findings revealed a gap between service quality level expected by customers and actually what they perceive except in the case of tangibility, where perceived quality surpasses expectations. The study revealed that there is a constructive and significant control of multidimensional SERQUAL scale on customer satisfaction. The findings will help automobile market players to get insights about quality perception of customers and help to meet customer expectations.
Keywords: quality; service; customer satisfaction; automobiles; Toyota; India